Comparison of Heparin Dressing versus Saline Dressing for Pain Relief at Split Thickness Skin Graft Donor Site - Younas, Aqsa; Bashir, Mustehsan; Afzal, Omar; Aslam, Tayyeba (Biological and Clinical Sciences Research Journal, 2025)
Split-thickness skin grafting (STSG) is a widely used reconstructive technique for treating various soft tissue defects. Objective: To compare the efficacy of heparin dressing versus saline dressing in terms of pain relief, healing time, complications, and patient satisfaction at split-thickness skin graft donor sites. Methodology: This prospective comparative study was conducted at Mayo Hospital, Lahore, from September 2024 to February 2025. A total of 320 patients undergoing STSG were enrolled and randomly divided into two groups: Group A (heparin dressing, n = 160) and Group B (saline dressing, n = 160). Pain was assessed using the Visual Analog Scale (VAS) on postoperative days 1, 3, 5, and 7. Healing time, complications, and patient satisfaction were also recorded. Results: The mean pain scores were significantly lower in the heparin group across all postoperative days (Day 1: 6.8 ± 1.2 vs 7.4 ± 1.3; Day 7: 1.2 ± 0.6 vs 2.5 ± 0.7; p < 0.001). The average healing time was shorter in the heparin group (8.3 ± 1.4 days) compared to the saline group (10.1 ± 1.6 days; p < 0.001). Delayed healing occurred in 6.3% of heparin-treated patients, compared with 15.6% in the saline group (p = 0.02). Patient satisfaction was higher with heparin dressings (87.5% vs 68.1%; p < 0.001), while infection rates were low and comparable between groups. Conclusion: It is concluded that heparin dressing provides superior outcomes compared to saline dressing for donor site management in split-thickness skin grafts. It significantly reduces postoperative pain, accelerates epithelialization, and enhances patient comfort without increasing complications.